2002
DOI: 10.1002/dvdy.10203
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal expression of folate‐binding protein 1 (Fbp1) is closely associated with anterior neural tube closure in mice

Abstract: Periconceptional folate supplementation is widely believed to have significant preventive effects on the production of neural tube defects. Folate-binding protein 1 (FBP1) is one of the membrane proteins that mediate cellular uptake of folate. Although recent studies suggest that Fbp1 is essential for neural tube closure, the pattern of Fbp1 expression in embryonic tissues has not been examined in detail. To elucidate how Fbp1 contributes to neural tube closure, we examined the spatial and temporal expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
64
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 38 publications
6
64
1
Order By: Relevance
“…To confirm that these results were consistent with the true distribution of Folr1 at the time of neural crest formation/migration, we used the public domain morphometric analysis system NIH Image to test the distribution of anti-FOLR1 antibody in the HH stage 17 embryo. The results showed that 72% of the labeling for FOLR-positive cells were in the neural tube and 18% was in the neural crest, supporting further the probability that the qPCR-detected decline in Folr1 reflected an siRNA knockdown effect specific to these regions; and confirming earlier reports on the spatial distribution of the folate receptor (Saitsu et al, 2003;Sato et al, 2008).…”
Section: Folate Receptor Knockdown and Nc Migration 1139supporting
confidence: 86%
See 3 more Smart Citations
“…To confirm that these results were consistent with the true distribution of Folr1 at the time of neural crest formation/migration, we used the public domain morphometric analysis system NIH Image to test the distribution of anti-FOLR1 antibody in the HH stage 17 embryo. The results showed that 72% of the labeling for FOLR-positive cells were in the neural tube and 18% was in the neural crest, supporting further the probability that the qPCR-detected decline in Folr1 reflected an siRNA knockdown effect specific to these regions; and confirming earlier reports on the spatial distribution of the folate receptor (Saitsu et al, 2003;Sato et al, 2008).…”
Section: Folate Receptor Knockdown and Nc Migration 1139supporting
confidence: 86%
“…Therefore, we designed experiments to assess the role of the avian homolog of Folr1 during neural crest formation. We determined that the folate receptor gene Folr1 was highly expressed in the avian model in the neural crest and neural tube during neurulation, consistent with the results shown by Saitsu et al (2003) in the mammalian embryo during similar stages of development. Subsequently, we inserted by means of electroporation an short-interfering RNA (siRNA) directly into the neural tube at the site of formation of the premigratory cardiac neural crest.…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations
“…by 30–70% (Laurence et al 1981; Smithells et al 1983; Mulinare et al 1988; Mills et al 1989; Milunsky et al 1989; MRC Vitamin Study Research Group 1991; Saitsu et al 2003), leading to an international consensus on the importance of preconceptional FA supplementation. In Japan, despite the efforts of JSOG and JAOG, preconceptional FA supplementation was not universally accepted.…”
Section: Communication Of Fa Intake Recommendationsmentioning
confidence: 99%